Investigação da capacidade da zeólita natural para remoção de nitrogênio amoniacal - Valduga, Davi Marcos (2019)
The landfill leachate has several organic and inorganic substances with toxic potential that make it difficult to treat, such as ammoniacal nitrogen. Several physicochemical and biological technologies, such as adsorption, are employed in the treatment of leachate. In Serra Geral Group spills, in particular in the metropolitan region of Porto Alegre - RS, amyloid horizons occur, in varying degrees of alteration, with filling of the cavities with zeolites. The commercial extraction of these horizons (gravel) is destined to landfill or maintenance of roads, for its low cost and great demand. The adsorbent and cation exchange properties of zeolites are related to polarity, crystalline structure, composition, porosity and ion selectivity in the adsorption. The objective of this work was to characterize and investigate the adsorption capacity of ammonium ion in zeolites that occur in a gravel extraction in RS. The samples were subjected to chemical activation in 1M solutions of hydrochloric acid and sodium hydroxide and characterized for specific surface area, X - ray Diffraction (XRD), Infrared Region Adsorption Spectroscopy (FTIR), Microscopy scanning electron microscopy (SEM) and X-ray spectroscopy (FRX). The cation exchange tests evaluated the adsorption of ammoniacal nitrogen in aqueous solutions of ammonium chloride (solution B) and in dilute solution of landfill leachate (solution A). The results of the mineral characterization of the zeolite sample indicated a mixture of stilbite-laumontite at 84 % - 16 %. The FTIR analysis indicated bands from the Si-O-Al group for the ZN sample, but did not present a significant change in the structure modification in the identified bands and in their enlargements for the activated samples in relation to the natural sample. In the SEM analysis, it was possible to identify differences between the surface morphologies of the samples. The natural zeolite showed polycrystalline agglomerates. The sample treated with sodium hydroxide showed mineral particles with the surface apparently covered by sodium, whereas the sample activated with HCl showed corrosion of the particles and increase of the cavities in the polycrystalline agglomerates. The volume of mesopore and surface area was lower for sample activated with NaOH and higher for sample activated with HCl. The chemical composition of the natural sample was 45.18 % silicon oxide (SiO2) and 25.95 % aluminum oxide (Al2O3), with SiO2 / Al2O3 ratio of 1.74. This sample had impurities such as Fe2O3 and CaO, which may lead to a decrease in the ion exchange potential. All samples showed low Zeta Potential and negative charge, which allows the 11 adsorption of positively charged ions in the pH ranges from 4 to 7. The kinetic tests showed that the pseudo-first order model presented better adjustment to the experimental data. And the Freundlich isotherm model was the one that presented the best linear correlation. Ammonia loading was low. The best adsorption result was for the NaOH-activated sample, with a value of 0.326 mg.g-1 for solution B and 0.296 mg.g1 for solution A